2014
DOI: 10.1176/appi.ps.201300298
|View full text |Cite
|
Sign up to set email alerts
|

First Treatment Contact for ADHD: Predictors of and Gender Differences in Treatment Seeking

Abstract: Objectives For attention-deficit hyperactivity disorder (ADHD), treatment seeking is a critical first step in treatment initiation and remains insufficiently understood. The aims of this study were to estimate ADHD treatment-seeking probabilities over the lifetime and to identify predictors of treatment seeking for ADHD separately for males and females. Methods Data were drawn from 2001 to 2005 as part of the National Epidemiologic Survey on Alcohol and Related Conditions, a two-wave face-to-face survey cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Additionally, if an individual with SUD was not diagnosed with ADHD as a child, it is less likely that the behaviour as an adult will be linked to ADHD, because these are associated with intoxication, withdrawal or the (interpersonal) consequences of substance abuse [15]. As ADHD is mostly not the reason why patients with SUD seek treatment [16], it is the clinician’s task to address and recognize ADHD in these patients. Finally, many consequences of ADHD (job loss, poor school performance) are also seen in patients with SUD, and they can be erroneously attributed to substance abuse.…”
Section: Consensus Statement For the Screening And Diagnosis Of Adhd mentioning
confidence: 99%
“…Additionally, if an individual with SUD was not diagnosed with ADHD as a child, it is less likely that the behaviour as an adult will be linked to ADHD, because these are associated with intoxication, withdrawal or the (interpersonal) consequences of substance abuse [15]. As ADHD is mostly not the reason why patients with SUD seek treatment [16], it is the clinician’s task to address and recognize ADHD in these patients. Finally, many consequences of ADHD (job loss, poor school performance) are also seen in patients with SUD, and they can be erroneously attributed to substance abuse.…”
Section: Consensus Statement For the Screening And Diagnosis Of Adhd mentioning
confidence: 99%
“…Despite the effectiveness of evidence-based treatments and the long-term negative impact of untreated ADHD, the NCS-R revealed that only 51.8% of people who meet criteria for ADHD will ever make treatment contact (Wang et al, 2005). Data from the National Epidemiologic Survey on Alcohol and Related Conditions reported a similar predicted treatment rate, 55% (Dakwar et al, 2014). Additionally, the median delay from symptom onset to treatment for ADHD is estimated at 10.5 to 28 years with younger cohorts at the shorter end of the delay (Dakwar et al, 2014).…”
Section: Adhd Treatment Decision-makingmentioning
confidence: 82%
“…Data from the National Epidemiologic Survey on Alcohol and Related Conditions reported a similar predicted treatment rate, 55% (Dakwar et al, 2014). Additionally, the median delay from symptom onset to treatment for ADHD is estimated at 10.5 to 28 years with younger cohorts at the shorter end of the delay (Dakwar et al, 2014).…”
Section: Adhd Treatment Decision-makingmentioning
confidence: 82%
See 1 more Smart Citation
“…For borderline personality disorder, 60% have concurrently a mood disorder, 58% an anxiety disorder and 51% a substance use disorder (Grant et al, 2008). Concerning adults with attention deficit hyperactivity disorder (ADHD) in the general population, 49%-54% have concurrently a mood disorder, 50% have an anxiety disorder, 41%-59% have an alcohol use disorder and 53%-63% have a drug use disorder (Dakwar et al, 2014). Therefore, this high rate of comorbidity in psychiatry suggests that by assessing common MD, the sample would have also included individuals with other non-assessed disorders.…”
Section: Limitationsmentioning
confidence: 99%